Differences in Consumption of Food Sources that Inhibit and Enhance Iron Absorption in Adolescent Girls - Nadila, Amalina (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Anemia is a condition where the hemoglobin mass and the circulating erythrocyte mass cannot fulfill their function as oxygen providers for body tissues. This is caused by irregular consumption habits. The purpose of this study was to determine the difference in food consumption of iron inhibiting sources and the difference in food sources of iron absorbing facilitators in anemic and non-anemic adolescent girls at SMAN 1 Trenggalek. This type of research is case control or based on diseases suffered by research respondents with the design used is analytical observations. Data collection techniques were carried out by collecting sample identity data through questionnaires, food data on inhibitor and enhancer sources through Food Frequency Questionnaire (FFQ) type Semi Quantitative FFQ (SQFFQ), and Hb levels using Easy Touch GCHB Meter. The data analysis used is the T-Test test to determine whether there is a significant difference between the two samples. The results of the study stated that differences in food consumption of iron inhibitors and facilitators affect the condition of adolescent girls of SMAN 1 Trenggalek where students who often consume foods and drinks that are classified as inhibitors, such as (coffee and tea) will be indicated anemia. While schoolgirls who consume healthy foods and drinks, sufficient animal protein and vitamin C such as (citrus fruits, mangoes and papayas) in the body are fulfilled can avoid symptoms of anemia. So it can be concluded that there are differences in sources of inhibitors and facilitators of iron absorption in anemic and non-anemic adolescent girls at SMAN 1 Trenggalek.